RECONSTRUCTION OF REGULATIONS OF BATAM BUSINESS ENTITY GIVING PERMITS FOR INDUSTRIAL LOCATIONS AND SPECIAL ECONOMIC AREAS - sumardi noto utomo (Journal Philosophy of Law, 2022)
Reconstruction; Authority; Batam Business Entity; Giver of Special Economic Zone Industrial Location Permit. Indonesia’s national development aims to create a just and prosperous society. National development will be achieved if economic development can be implemented. Indonesia’s economic development is followed by industrial growth and development. With the transition of the legal umbrella status through the birth of Law no. 39 of 2009 concerning Special Economic Zones (SEZ), SEZ is an area with specific boundaries with geo-economic and geo-strategic advantages. It is given special facilities and incentives as an investment attraction. The formulation of the problem in this study is (1) Why is the authority of BP. Batam to give Industrial Location Permits regulated by the Special Economic Zone? (2) What is the Regulatory Authority of BP. Batam to issue a permit for the location of the Special Economic Zone Industry? (3) How to Reconstruct BP’s Authority. Batam is the issuer of the Special Economic Zone industrial location permit? Objectives (1) To find and analyze the concept of the Batam Concession Agency towards a Special Economic Zone; (2) To examine and analyze the Regulatory Authority of the Batam Concession Agency granting industrial location permits for Special Economic Zones; (3) To reconstruct the authority of the Batam Concession Agency that grants Industrial Location Permits. Special Economic Zones. From the perspective of the Positive Normative Law that applies in Indonesia; Research Approach: Using sociological juridical method; This research is included in the empirical juridical research. Research Results (1) Aspects, Philosophical Elements; Sociological elements; juridical elements. Research Results (2) Regulation, Law Number 39 of 2009 concerning Special Economic Zones, Jo. Act. Number 11 of 2020 concerning job creation. Research Results (3) Reconstruction, Needs to be reviewed regarding Presidential Decree No. 41 of 1973 concerning industrial areas along with the Act. No. 39 of 2009 concerning Special Economic Zones: Elucidation of Articles 36 and 38. This will result in maladministration and closer to corruption. Conclusion: Presidential Decree Number 41 of 1973 concerning Batam Island Industrial Area, Article 1 paragraph (2) It is not in line with current expectations. No adjustments have been made to the Riau Islands Province Spatial Plan and/or Regency/City Spatial Plan, which can be seen in the Act. No. 39 of 2009 concerning Special Economic Zones: Elucidation of Articles 36 and 38 can result in maladministration.